CRIMINAL LIABILITY FOR SOCIAL HATRED AND ENMITY INSTIGATION, DIFFICULTIES WITH THEIR THEORETICAL AND PRACTICAL APPLICATIONS - Treļs, Ēriks (Administrative and Criminal Justice, 2015)
After the Latvian Republic’s accession to the European Union on 1st May 2004, the interaction between representatives of different race, color, nationality, ethnic origin, religion or culture increased and continues to grow with each year. The communication experience and lack of information is a breeding ground for prejudice and violence. The unfavorable economic situation and social challenges are promoting prejudice, intolerance, racism and discrimination. On 25 September 2014, amendments were made to the Criminal Law in Latvia, which improved the regulatory framework in relation to the so-called “hate crimes”, with liability for social hatred and enmity. The article aims to initiate a debate on potential problems related to the application of the Section 150 of the Criminal Law. The author offers his vision of the new regulatory framework application problems.